Functional Compromise in the Middle Vault in the Management of Revision Rhinoplasty - Wang, Leo; Friedman, Oren (Facial Plastic Surgery, 2018)
As rhinoplasty procedures become more common, the need for revision surgeries increases as well. Unlike primary rhinoplasties, revision rhinoplasties can be more challenging because of anatomic differences from initial surgery, a lack of available cartilage, tissue remodeling responses, and other complications. As such, surgeons should be prepared to address revision rhinoplasty patients differently from primary rhinoplasty patients. Here, the authors describe a generalizable approach to revision functional rhinoplasty patients and detail some of the surgical techniques that can be employed to achieve optimal outcomes, with particular attention paid to procedures that can be used in the middle vault.
Keywords: rhinoplasty; revision; nasal surgery; nasal valve collapse; nasal obstruction